Ekowisata, Wisata Religi-Spritual: Sebagai Cara untuk Mewujudkan Pariwisata Berkelanjutan - Mardani, Dede Aji (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
When we talk about the topic of the spiritual dimension of tourism, one of the most important issues to ask is how people search for the meaning of their lives, as well as their subjective experience and sense of connectedness, when they are away from home. In fact, there is a close relationship between tourism and religion, which is and has always been a significant driving force behind travel, from the early days of pilgrimage to modern day trips to holy places. Followers of religions with strong belief systems, as well as travelers with only a passing interest in the topic, consider religious sites, rituals, festivals and ceremonies to be among the most important attractions. People who have recently started participating in spiritually-driven experiences, as well as people who want to build sustainable greatness through travel, have made spiritual tourism experiences increasingly popular. It is possible that these qualities are the main cause of the recent surge in popularity of this trend. In contrast to common conceptions of pilgrimages and religious tourism, traveling can be beneficial to one's spiritual development for a number of different reasons. Despite the fact that religious tourism and the spiritual connection to a location are wide-ranging, few scholars have investigated the complex interactions between religion, spirituality and environmentally responsible tourism. The social, societal and ecological implications of (mass) religious tourism is a topic that has received relatively little attention in the world of academic research. Some authors have highlighted the adverse impact that religious tourism has on the commercialization of places and objects that were previously considered sacred. Researchers should pay attention to the commodification of religious symbols and the economic implications of selling these symbols as the world becomes more consumer-oriented